Feto-maternal outcome of oligohydramnios in tertiary care hospital - Prajapati, Shetal; Johar, Sakina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The importance of amniotic fluid volume as an indicator of fetal wellbeing has made its assessment an important part of antenatal fetal surveillance. Oligohydramnios complicates 0.5% to 8% of pregnancies and the prognosis for pregnancies complicated by oligohydramnios is dependent on the gestational age and the underlying aetiology. This study aims to determine the feto-maternal outcome of oligohydramnios in a tertiary care hospital. Methods: In this study, we included 100 patients of oligohydramnios, with AFI ≤5 cm with a singleton pregnancy with intact membranes. The maternal outcome was accessed by mode of delivery and maternal complications and the neonatal outcome was studied by birth weight, APGAR score, NICU admission and perinatal mortality. Results: PIH was the most common risk factor in 38% of cases followed by IUGR in 29%, doppler changes in 24%. The reduced diastolic flow was the most common abnormal doppler finding in the 23% abnormal doppler cases, from which 39% underwent cesarean section, 9% required NICU admission and 61% had neonatal death. 53% delivered by cesarean section of which 13% had neonatal death. NICU admission is required in 64% of cases. Conclusions: We conclude that oligohydramnios is a high-risk pregnancy and proper antepartum care, intensive fetal surveillance and intrapartum care are required in a patient with oligohydramnios. Every case of oligohydramnios needs careful antenatal evaluation, parental counselling, individualization, decisions regarding time and mode of delivery. Continuous intrapartum fetal monitoring and good neonatal care are necessary for a better perinatal outcome.